Indonesia EFL Teachers' Perceptions about Teaching English as Lingua Franca - Gupuh Rahayu (Language-Edu, 2020)
AbstractAs the requirement of English mastery becomes rapidly high in this globalization era, an English teacher plays the first role in students’ learning development because in a country whose English as a foreign language become the essential source of language input. Meanwhile, ELF as the development of English which emerge in South-East Asia may help the EFL teachers in delivering their teaching learning material in EFL classroom. As for how the EFL teachers’ perceptions about the emerge ELF recently, this study aims to investigate Indonesia EFL Teachers’ perceptions about teaching English as Lingua Franca. By conducting a survey study, the researcher gained the EFL teachers’ perceptions about teaching English as Lingua Franca. The questionnaire as the source of data in this study was distributing to 15 EFL teachers in the city of Tulungagung. The researcher also doing an interview with three of those teachers. Most of EFL teachers’ who participated in this study have less knowledge about ELF, but more than half of them agreed with the statement given that clarify as ELF. The participants also see ELF as an interesting development of English to bring a new performance in their teaching learning classrooms.Keywords: EFL teachers, perceptions, ELF.